2023
DOI: 10.3390/metabo13040577
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear Magnetic Resonance Spectroscopy at Ultra-High-Field: Assessing Human Cerebral Metabolism in Healthy and Diseased States

Abstract: The brain is a highly energetic organ. Although the brain can consume metabolic substrates, such as lactate, glycogen, and ketone bodies, the energy metabolism in a healthy adult brain mainly relies on glucose provided via blood. The cerebral metabolism of glucose produces energy and a wide variety of intermediate metabolites. Since cerebral metabolic alterations have been repeatedly implicated in several brain disorders, understanding changes in metabolite levels and corresponding cell-specific neurotransmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 205 publications
0
2
0
Order By: Relevance
“…This assumption would be consistent with our findings, as we did not observe any significant changes in FA. We could not detect any change in the concentration of NAA, which is considered a marker for neuronal functionality, and a decrease in the NAA levels occurs in advanced Alzheimer's disease [54], [55], which is also related to a decrease in the volume of the hippocampal region of the brain. In our study, we observed the reduction of the hippocampal region without the reduction in NAA concentration in the measured part of this region, but an increase in mIns was observed.…”
Section: Resultsmentioning
confidence: 57%
“…This assumption would be consistent with our findings, as we did not observe any significant changes in FA. We could not detect any change in the concentration of NAA, which is considered a marker for neuronal functionality, and a decrease in the NAA levels occurs in advanced Alzheimer's disease [54], [55], which is also related to a decrease in the volume of the hippocampal region of the brain. In our study, we observed the reduction of the hippocampal region without the reduction in NAA concentration in the measured part of this region, but an increase in mIns was observed.…”
Section: Resultsmentioning
confidence: 57%
“…Thus, this review focuses on those cellular barriers to glucose delivery and does not address the end stage glucose utilization at the levels of the brain, muscles, heart, and other key glucose consumers. The reader is referred to recent scholarly reviews on those topics (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%